A Freirean interrogation of creativity beliefs. Issue 1 (2nd January 2021) - Sosa, Ricardo; Connor, Andy
ABSTRACT: Creativity is considered here as a universal and diverse capacity that is central to full human agency. This view contrasts with beliefs that negate one's creativity and that of others. Self-reports of creativity are examined in this paper taking inspiration from the study of oppression and liberation in the praxis of social change by the influential education theorist Paulo Freire. An exploratory survey of one hundred and fifty-nine professionals examines the types of perceptions and beliefs that designers and non-designers have about their own creativity, the creativity of others, and how they explain the nature of creativity. Based on how respondents explain their own creative capacities and those of others, three initial categories are formulated based on theories of social change: oppressive, oppressed, and liberating views of creativity. The findings demonstrate how these categories can be interpreted and implications for future work are discussed in the closing section.